Why should we care about sound symbolism in EFL learning?: Two pilot studies - Roig-Marín, Amanda (International Journal of English Studies, 2017)
Given the importance of the phonological and lexical components of the language in L2 learning, this article discusses an innovative, holistic approach to learning these two components of the language based on the existence of “sound symbolism”—the interrelation between sound and meaning—in English. In particular, it describes how and why the study of sound symbolism can be advantageous to EFL learners. This claim is grounded in empirical data gathered from two pilot studies carried out in two educational settings (a secondary school and the University of Alicante). The results suggest that knowledge of sound symbolic principles underlying the English language can enhance lexical storage and semantic prediction